Assessing the impact of China's timber industry on Congo Basin land use change. Issue 2 (27th June 2018) - Fuller, Trevon L.; Narins, Thomas P.; Nackoney, Janet; Bonebrake, Timothy C.; Sesink Clee, Paul; Morgan, Katy; Tróchez, Anthony; Bocuma Meñe, Demetrio; Bongwele, Eddy; Njabo, Kevin Y.; Anthony, Nicola M.; Gonder, Mary Katherine; et al.
Abstract : Through the rise of global commodity chains, consumer demand in China and the USA has given rise to the extraction of natural resources in the Congo Basin. The Chinese market for high‐valued animal products such as elephant ivory and pangolin scales has encouraged poaching, exploitation and trafficking of these goods in Africa. Chinese demand for other African commodities, however, remains less well known. Using data across a 15‐year period (2001–2015), we analysed the relationship between Chinese timber imports and tree‐cover loss in the Congo Basin. Tree‐cover loss was measured via remote sensing and the value of imports was obtained from official trade statistics. Results indicate that the total accumulated export of wood from Congo Basin countries to China doubled between 2001 and 2015, with 50% of exports originating from Cameroon and the Republic of Congo. We found a positive relationship between measures of Chinese logging and the loss of tree cover in the Congo Basin. Further investigation of the timber products market showed that US demand for Chinese‐made furniture was positively correlated with Chinese timber imports from the Congo Basin. These findings suggest that US demand for furniture encourages Chinese economic actors to harvest timber from Congo Basin forests. Our results help to illuminate the complex environmental and economic drivers surrounding trade and deforestation and can help inform consumers about more sustainable ways to purchase wood products from one of the world's preeminent biodiversity hotspots.